A Critical Function for the Transcription Factors GLI1 and GLI2 in the Proliferation and Survival of Human Mast Cells - Falduto, Guido Hernan; Pfeiffer, Annika; Zhang, Qunshu; Yin, Yuzhi; Metcalfe, Dean Darrel; Olivera, Ana (Frontiers in Immunology, 2022)
Mast cell hyperactivity and accumulation in tissues are associated with allergy and other mast cell-related disorders. However, the molecular pathways regulating mast cell survival in homeostasis and disease are not completely understood. As glioma-associated oncogene (GLI) proteins are involved in both tissue homeostasis and in the hematopoietic system by regulating cell fate decisions, we sought to investigate the role for GLI proteins in the control of proliferation and survival of human mast cells. GLI1 transcripts were present in primary human mast cells and mast cell lines harboring or not activating mutations in the tyrosine kinase receptor KIT (HMC-1.1 and HMC-1.2, and LAD2 cells, respectively), while GLI2 transcripts were only present in HMC-1.1 and HMC-1.2 cells, suggesting a role for oncogenic KIT signaling in the regulation of GLI2. Reduction in GLI activity by small molecule inhibitors, or by shRNA-mediated knockdown of GLI1 or GLI2, led to increases in apoptotic cell death in both cultured human and murine mast cells, and reduced the number of peritoneal mast cells in mice. Although GLI proteins are typically activated via the hedgehog pathway, steady-state activation of GLI in mast cells occurred primarily via non-canonical pathways. Apoptosis induced by GLI silencing was associated with a downregulation in the expression of KIT and of genes that influence p53 stability and function including USP48, which promotes p53 degradation; and iASPP, which inhibits p53-induced transcription, thus leading to the induction of p53-regulated apoptotic genes. Furthermore, we found that GLI silencing inhibited the proliferation of neoplastic mast cell lines, an effect that was more pronounced in rapidly growing cells. Our findings support the conclusion that GLI1/2 transcription factors are critical regulators of mast cell survival and that their inhibition leads to a significant reduction in the number of mast cells in vitro and in vivo, even in cells with constitutively active KIT variants. This knowledge can potentially be applicable to reducing mast cell burden in mast cell-related diseases.